Pre-operative serum TSH level estimation for predicting malignant nodular thyroid disease - Hamdi, Kotaiba Kh.; Ghadhban, Basim R.; Turkey, Hussein Ali; Sulaiman, Tharwat I. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: the aim of this study was to assess the value of serum thyroid–stimulating hormone (TSH) levels in predicting malignancy in patients with nodular thyroid disease (NTD). Objective: The aim was to examine the relationship between preoperative TSH and differentiated thyroid cancer (DTC). Patients and Method: all patients with NTD who were admitted in the first surgical unit of Baghdad teaching hospital and assessed for preoperative TSH level before subjecting them for thyroidectomy from first of April 2014 to 31 of January 2016, were included in the study. A preoperative database sheets including Age, gender, nodule size, and pathology were evaluated. Logistic regression analysis was used to determine which factors were predictive of malignancy. Results: 291 patients were included in our study after exclusion of 20 patients, Four patients with histopathological results other than differentiated thyroid cancer (anaplastic, medullary carcinoma) and sixteen patients were on thyroxine therapy. The overall rate of malignancy was 11%. The rate was slightly higher at extremes of age .the mean TSH was higher in the malignant group (2.07 vs 1.07, p=0.02). The rate of malignancy was 40% in patients with TSH level > 5.5 μIU/mL. Logistic regression analysis revealed that TSH level was the only significant risk factor for malignancy. Conclusion: the serum TSH level may be useful in predicting the probability of cancer and optimizing the extent of thyroidectomy in patients with NTD. هدف الدراسة: تقدير مستوى الهرمون المحفز للغدة الدرقية قبل العملية للتنبؤ بوجود السرطان في امراض الغدة الدرقية العقدية. المرضى والطرق : جميع المرضى الذين يعانون من امراض الغدة الدرقية العقدية الذين تم قبولهم في وحدة الجراحة الأولى من مستشفى بغداد التعليمي وتقييم مستوى الهرمون المحفز للغدة الدرقية(TSH) قبل إخضاعهم لعملية استئصال الغدة الدرقية ‘ تم ادراجهم في هذه الدراسة من الأول من نسيان 2014 إلى 31 من كانون الثاني 2016. تم تقييم أوراق قاعدة البيانات قبل الجراحة بما في ذلك العمر والجنس وحجم العقد، و التحليل النسيجي بعد اجراء الجراحة. تم استخدام تحليل الانحدار اللوجستي لتحديد العوامل التنبؤية في ايجاد سرطان الغدة الدرقية المتميز. النتائج : بعد ادخال مئتان وواحد وتسعون مريض في الدراسة‘ تم استبعاد اربعة مرضى لوجود سرطان الغدة الدرقية غير المتميز في نتائج تحليل الفحص النسيجي النهائي ‘ وتم استبعاد ستة عشر مريض اخرين لتعاطيهم دواء الثايروكسين . معدل السرطان %11 ، المعدل مرتفع قليلا في نقيض العمرين (اقل من 30 سنة واكثر من سبعين سنة) ، معدل مستوى هرمون ( (TSHكان اعلى عند مرضى سرطان الغدة الدرقية ) 2.07 vs1.07, p=0.02) . كانت نسبة السرطان %40 عند المرضى الذين مستوى الهرمون المحفز (TSH) لديهم اكثر من 5.5 µIU/ml . بين تحليل الانحدار الوجيستي ان مستوى الهرمون المحفز للغدة الدرقية هو العامل الوحيد القادر على تنبئ وجود سرطان الغدة الدرقية المتميز. الاستنتاجات : تقييم مستوى الهرمون المحفز للغدة قبل العملية مفيد في تنبئ احتمالية وجود سرطان الغدة المتميز وتحسين مستوى استئصال الغدة لدى مرضى الغدة الدرقية العقدية.